Graphene, nanotube & organic materials composites for transparent conductor and electrical device applications - Kwan, Garen Yue Chau (2016)
Heralded as the next miracle material, graphene oxide (GO) has the potential to be used in a variety of next generation devices. However, there are still gaps in the fundamental knowledge on this material and even now, a canonical model of GO has not been developed. The two aims of this thesis are to support the development of the canonical model by studying the O 1s1/2 spectra of GO and to develop the use of reduced GO for electronic device applications. Here, the identities of peaks in the O 1s1/2 spectrum were identified by chemical and mathematical analysis and the fabrication processes were made environmentally friendly and industrially scalable by the use of ascorbic acid for low temperature reduction of GO and ultrasonic spray coating for large area deposition respectively in transparent conducting electrodes (TCE). Further to this, the conductive character of reduced GO was also utilized in a bilayer device design with phthalocyanines for a NO2 sensing application. The binding energy of O 1s1/2 electrons in the carbonyl, carboxyl, hydroxyl and epoxy functional groups were found to be 530.9, 532.3, 533.1 & 534.4 eV respectively. With this information, metastability in GO was understood to result in the preferential formation of the carboxyl functional group, which cause vacancies in the graphene flake and are difficult to remove, during the thermal reduction of GO. This was estimated to occur between the temperatures of 543 & 561 K and it is recommended that thermal reduction methods keep below this temperature range. A TCE with a figure of merit of 189.9 was fabricated when GO reduced by ascorbic acid was used in conjunction with silver nanowires (AgNW) in a bilayer TCE. The reduced GO over layer was observed to retard AgNW degradation caused by capillary instability and this was achieved by protecting the surface of the nanowire from oxygen. This reduced surface diffusion of the silver atoms and extended the lifetime of the nanowires. Finally, a new bilayer gas sensing device utilizing phthalocyanines on reduced GO was described and tested. The bilayer design improved device currents, with no loss in normalized sensitivity and a theoretical model that was developed to describe it. In summary, a deficiency in the literature of GO was identified & solved and this finding will be a useful tool in the development of a canonical model for GO. The identification of the O 1s1/2 peaks of the different functional groups will also aid in the characterization of reduced GO with low C/O ratios, typically found in highly reduced GO. The main challenges preventing the widespread use of GO in electronic devices were identified to be device design and fabrication techniques. GO is a versatile material platform which can be used in a variety of applications, but a deep understanding of both GO properties and the properties of complementary materials is required so that the right device design can be employed to harness the desirable characteristics of these materials. Future work will focus on the development of the canonical model, consider methods of increasing the FOM of TCEs fabricated using reduced GO, confirm the stability of the bilayer device and expand the use of GO into other devices.